2004
DOI: 10.1111/j.0105-2896.2004.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐12 and IL‐23: master regulators of innate and adaptive immunity

Abstract: Initiation of an effective immune response requires close interactions between innate and adaptive immunity. Recent advances in the field of cytokine biology have led to an increased understanding of how myeloid cell-derived factors regulate the immune system to protect the host from infections and prevent tumor development. In this review, we focus on the function of interleukin (IL)-23, a new member of the IL-12 family of regulatory cytokines produced by activated macrophages and dendritic cells. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
579
2
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 674 publications
(604 citation statements)
references
References 92 publications
13
579
2
10
Order By: Relevance
“…IL-12, which was first described as natural killer cell stimulatory factor, 10 is a primary inducer of the development of T-helper 1 (Th1) lymphocytes characterized by the production of IFNg, and IL-23 drives the development of Th17 lymphocytes characterized by the production of IL-17. 11 There is a growing body of evidence for a key role of IL-12 in the immune response directed against Plasmodium species, whereas IL-23 was only recently proposed to be involved in malaria. 12 Neutralization of endogenous IL-12 with anti-IL-12p40 and anti-IL-12p35 antibodies in P. chabaudiinfected mice resulted in an increase of parasitemia, 13 whereas administration of recombinant IL-12 in mice and monkeys conferred a protection from Plasmodium species infection.…”
Section: Introductionmentioning
confidence: 99%
“…IL-12, which was first described as natural killer cell stimulatory factor, 10 is a primary inducer of the development of T-helper 1 (Th1) lymphocytes characterized by the production of IFNg, and IL-23 drives the development of Th17 lymphocytes characterized by the production of IL-17. 11 There is a growing body of evidence for a key role of IL-12 in the immune response directed against Plasmodium species, whereas IL-23 was only recently proposed to be involved in malaria. 12 Neutralization of endogenous IL-12 with anti-IL-12p40 and anti-IL-12p35 antibodies in P. chabaudiinfected mice resulted in an increase of parasitemia, 13 whereas administration of recombinant IL-12 in mice and monkeys conferred a protection from Plasmodium species infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, other pro-inflammatory mediators produced by the Th IL-17 cells, including TNF-α, IL-6, IL-8 and other chemokines (Kolls & Linden 2004, Langrish et al 2004, may also play a significant role in the pathology. One apparent mechanism used by Th IL-17 cells to cause pathology is through recruitment of granulocytes, which in the case of the schistosome egg-granulomas, may include the eosinophils.…”
mentioning
confidence: 99%
“…7,30 Stat4 is essential for IL-12-mediated responses including perforin-mediated NK cell activity, 31,32 whereas Stat3 may be involved in mediating more general types of signals such as those for cell growth and survival. 33,34 It was recently reported that the expression of IL-23 was increased in a human tumor, and that the growth of the transplanted tumor was restricted in mice depleted for IL-23p19 or IL-23R.…”
Section: Differential Antitumor Effects Of Il-23 H-t Jin Et Almentioning
confidence: 99%